Preputial balanitis xerotica obliterans shortly after hand, foot and mouth disease in a 5-year-old boy: Coincidence or consequence? - Zlatan, Zvizdic (2021)
Balanitis xerotica obliterans (BXO), a genital form of lichen sclerosus (LS) in males, is a progressive, sclerosing, inflammatory dermatosis affecting the foreskin, frenulum, glans penis, meatus, and urethra. BXO was considered a disease of adulthood until 1962 when Catterall and Oates reported the first case of isolated BXO of the prepuce in a 7-year-old child.1 The exact cause and etiology of BXO remain unknown. However, autoimmune dysregulation, various infections, genetic predisposition, chronic irritation through urine exposure, and hormonal influences have been associated with the development of BXO.2 Recent studies indicate that BXO is more common than previously thought to cause acquired phimosis and meatal stenosis.3 However, despite an increasing rate of diagnosis of BXO in children, little is known regarding the potential for associated comorbidities or an association with various human viruses. To the best of our knowledge, no cases of hand, foot, and mouth disease (HFMD) associated with BXO have been reported so far. A 5-year-old boy was referred to our department with an 8-month history of a painless progressive inability to retract the foreskin of the glans penis.